Two new Eastern North American species of the Aleiodes coxalis (Spinola) species-group (Hymenoptera: Braconidae, Rogadinae) reared from Geometridae - Shaw, Scott R.; Marsh, Paul M. (Zootaxa, 2004)
Two new species in the Aleiodes coxalis species-group are described from eastern North America: Aleiodes itamevorus and Aleiodes maritimus. Both are primary koinobiont parasitoids of Geometridae caterpillars, utilizing hosts from the genera Itame and Semiothisa.